A Review on Aerosol Drug Delivery: Fundamentals, Classifications, Particle Size Analysis and the Engagement of Nanoparticulate Systems - El-Maradny, Hoda Ahmed; Mneimneh, Amina T. (Drug Delivery Letters, 2022)
Background: The pulmonary route of administration has shown viability and effectiveness in local and systemic delivery, as a non-invasive method, not only for active pharmaceutical ingredients but also for genes, proteins, and enzymes for pulmonary and non-pulmonary diseases. Objectives: Nanoparticulate systems such as liposomes, solid lipid nanoparticles, nanostructured lipid carriers, emulsions, nanosuspensions, polymeric nanoparticles, and metal-based have been investigated as delivery carriers for the lungs. Nanoparticulate drug delivery systems are known for their optimum small size and suitability for pulmonary absorption as it is well recognized that drug particles within the size range of 1-5 μm are the best for pulmonary deposition. Results: The advantages of these colloidal systems are generated by their small size, large surface area, and rapid absorption. These systems are characterized by ease of preparation as inhalable formulation, the ability to increase drug concentration at the site of disease, preventing and minimizing drug loss and degradation, and the possibility of cell targeting. Conclusion: This article provides a brief review of the features of different aerosol devices, their advantages, limitations, and methods utilized for particle size analysis with a focus on the emerging field of nanocarriers as vehicles for pulmonary delivery for various lung disorders.
Keywords: pulmonary